Music Self-Efficacy for Performance: An Explanatory Model Based on Social Support - Zarza-Alzugaray, Francisco Javier; Casanova, Oscar; McPherson, Gary E.; Orejudo, Santos (Frontiers in Psychology, 2020)
The capacity of self-efficacy for explaining personal achievement in various contexts has made it one of the most researched psychological constructs in the field of educational research. Personal perceptions of self-efficacy are particularly relevant in the field of music performance, which is oriented toward the outward expressions of one’s own ability through public performances. Further personal variables, such as social support or music performance anxiety, which have been shown to be associated with musical success, are also relevant for research that seeks to understand the four sources of self-efficacy (mastery experiences, vicarious observation, verbal persuasion, physiological states) that are integral components of Bandura’s (2000) Social Learning Theory. Previous research, along with observed differences among musicians associated with educational level (Pre-University or University Degree) and gender (male-female) underpin the context of this study, which presents evidence regarding the factors that are capable of mediating perceptions of self-efficacy for musical performance. Specifically, the main objective of this study was to compare, by means of structural equation modeling, the mediating role of different personal variables in music self-efficacy for performance. We found that certain gender differences are significantly associated with the influence of social support on self-efficacy. Further research shall be required in order to improve pedagogical methods and help teachers increasingly individualize their teaching.